2022
DOI: 10.3389/fncel.2022.1025708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of neuronal death in brain injury after subarachnoid hemorrhage

Abstract: Subarachnoid haemorrhage (SAH) is a common cerebrovascular disease with high disability and mortality rates worldwide. The pathophysiological mechanisms involved in an aneurysm rupture in SAH are complex and can be divided into early brain injury and delayed brain injury. The initial mechanical insult results in brain tissue and vascular disruption with hemorrhages and neuronal necrosis. Following this, the secondary injury results in diffused cerebral damage in the peri-core area. However, the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 160 publications
0
16
0
Order By: Relevance
“…Poor-grade aSAH is a common neurosurgical cerebrovascular disease that threatens human health. Most patients with poor-grade aSAH experience direct damage to the brain tissue, secondary damage such as cerebral vessel spasm, secondary brain swelling, bleeding from reruptured aneurysms, and refractory fever ( 7 , 12 ). Patient mortality has declined in recent decades with improvements in neurocritical care management, such as multimodal monitoring, the use of CTA, controlled decompression, and hypothermia, patient mortality has declined.…”
Section: Discussionmentioning
confidence: 99%
“…Poor-grade aSAH is a common neurosurgical cerebrovascular disease that threatens human health. Most patients with poor-grade aSAH experience direct damage to the brain tissue, secondary damage such as cerebral vessel spasm, secondary brain swelling, bleeding from reruptured aneurysms, and refractory fever ( 7 , 12 ). Patient mortality has declined in recent decades with improvements in neurocritical care management, such as multimodal monitoring, the use of CTA, controlled decompression, and hypothermia, patient mortality has declined.…”
Section: Discussionmentioning
confidence: 99%
“…In aSAH, cerebral ischemia is a major cause of morbidity and mortality [ 21 ]. Generally, the rapid extravasation of blood after an aneurysm rupture will lead to a significant increase in intracranial pressure induced by acute hypoperfusion, leading to the continuous damage of cerebral perfusion pressure and a decrease in cerebral blood flow, eventually leading to cerebral ischemia and neuronal necrosis [ 22 , 23 , 24 ]. Therefore, the question before neurosurgeons is whether patients with ruptured aneurysms have a higher probability of postoperative cerebral ischemia when ICAS is found in preoperative CTA.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PGC-1α, NRF-1, and TFAM are closely related to mitochondrial biogenesis, and PGC-1α is involved in the regulation of mitochondrial energy metabolism ( Ahn et al, 2008 ; Dai et al, 2014 ). Animal experiments have demonstrated mitochondrial biogenesis regulated by SIRT3 in haemorrhagic and ischaemic stroke; however, further studies are required to confirm its role in other types of brain injury ( Liu L. et al, 2021 ; Chen J. et al, 2022 ). Additionally, mitophagy plays different roles in different environments, exhibiting a two-sided role in several types of brain injury.…”
Section: The Function Of Sirt3 In Brain Injurymentioning
confidence: 99%
“…Recent evidence has shown that SIRT3-targeted therapy can reduce postoperative cognitive impairment by reducing microglial activation and neuroinflammation in the hippocampus ( Ye et al, 2019 ; Liu Q. et al, 2021 ). The release of proinflammatory cytokines aggravates damage to the blood-brain barrier, accompanied by neuronal apoptosis, resulting in irreversible neurological damage after SAH ( Fan et al, 2017 ; Chen J. et al, 2022 ). According to in vivo and in vitro studies, SIRT3 deletion can worsen brain inflammation and blood-brain barrier damage after ischaemic stroke.…”
Section: The Function Of Sirt3 In Brain Injurymentioning
confidence: 99%